Equine Coronavirus: An Infectious Disease Affecting Florida Horses - Sally DeNotta; Linda Mittel (EDIS)
This publication provides an overview of equine coronavirus and discusses prevalence, transmission, clinical disease, diagnostic sampling, testing, and handling, treatment, prognosis, prevention and biosecurity, and potential for transmission to other species. Written by Sally DeNotta and Linda Mittel, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, January 2023.